Analisis peranan guru terhadap motivasi belajar IPA siswa melalui pendekatan model ARCS: Kajian literatur - Azizah, Siti Nurul Laili; Agusminarti (Journals of Indonesian Multidisciplinary Research, 2024)
Learning motivation is a crucial factor that determines students' success in science education. The role of teachers in fostering student motivation is essential for creating effective and meaningful learning experiences. This study aims to analyze the role of teachers in enhancing students' motivation to learn science through the application of the ARCS model. The method employed was a systematic literature review (SLR) analyzing fifteen scholarly articles published in accredited national journals. The findings reveal that teachers play a strategic role as facilitators, motivators, and classroom managers in improving student motivation. Internal factors such as the desire to succeed and student interest, as well as external factors like the use of innovative learning media, significantly contribute to learning motivation. The application of ARCS-based learning strategies and the integration of digital media such as virtual laboratories and Powtoon were proven effective in enhancing students' attention, relevance, confidence, and satisfaction. Based on these findings, it is recommended that teachers continue to develop learning approaches focused on student motivation to optimize science learning outcomes.